Recognizing ophiasis pattern in discoid lupus: a rare diagnostic challenge - Lamia Alakrash; Sara Alrabiah; Sawsan Alharthi (Dermatology Reports)
Lupus erythematosus is an autoimmune condition that can present in both cutaneous and systemic forms, with discoid lupus erythematosus (DLE) being the most prevalent type of chronic cutaneous lupus. Although the ophiasis pattern is well documented in alopecia areata, we present a rare case of DLE exhibiting this pattern in a 51-year-old Saudi female patient with a complex medical history, including systemic lupus erythematosus (SLE). This case underscores the importance of recognizing atypical presentations of DLE, which can lead to misdiagnosis and delays in treatment. We aim to enhance awareness among dermatologists regarding the diverse manifestations of DLE and encourage further investigation into such rare patterns.